Serum cortisol level after low dose dexamethasone suppression test may be predictive for diabetes mellitus and hypertension presence in obese patients: A retrospective study. (March 2020) - Hepsen, Sema; Sencar, Erkam; Sakiz, Davut; Akhanli, Pinar; Ucan, Bekir; Unsal, Ilknur; Ozbek, Mustafa; Cakal, Erman
Abstract: Aims: Obesity, a remarkably increased healthcare problem, accompanies with morbidities including type 2 diabetes mellitus (DM), hypertension, and cardiovascular diseases. Hypothalamic-pituitary-adrenal (HPA) axis alteration is thought to be effective on the background of obesity, even concomitant with DM and hypertension. We aimed to evaluate the negative feedback mechanism of the HPA axis via overnight 1 mg dexamethasone suppression test (DST) and the association of post-1 mg DST cortisol level with DM and hypertension presence in obesity. Methods: This study consisted of 402 obese patients who provide suppression after DST. Post-1 mg DST cortisol level and its association with other variables including anthropometric measurements, laboratory test results, hypertension, prediabetes, and DM presence were evaluated. Predictivity of post-1 mg DST for hypertension and DM was investigated. Results: We established a significant difference in post-1 mg DST cortisol level when compared patients with and without DM, patients without DM and with prediabetes, patients with prediabetes and DM (p < 0.001 vs. p = 0.003 vs. p = 0.022 respectively). Post-1 mg DST cortisol level was significantly higher in hypertensive patients (p < 0.001). Post-1 mg DST cortisol level had positive correlation with age (r = 0.319, p < 0.001), fasting plasma glucose (r = 0.168, p = 0.001), and HbA1c (r = 0.278, p < 0.001) levels. Logistic regression analyses demonstrated that post-1 mg DST cortisol level is an independent predictor of DM and hypertension presence. Conclusion: Cortisol negative feedback mechanism may be altered in obese patients who are complicated with hypertension and DM. Therefore, post-1 mg DST cortisol level can be predictive for hypertension and DM presence in obesity.